2016
DOI: 10.1002/fsn3.424
|View full text |Cite
|
Sign up to set email alerts
|

Waffle production: influence of batter ingredients on sticking of fresh egg waffles at baking plates—Part I: effect of starch and sugar components

Abstract: Fresh egg waffles are a sweet convenience product typically baked from eggs, water, sugar, flour, fat, leavening agents, emulsifiers, preservatives, and flavors. In industrial production, waffles are baked continuously in high amounts of up to 200 kg raw material per hour. Therefore, it is important that the waffles do not stick onto the baking plates, which can cause significant product loss and increased costs due to interruption of the baking process, required cleaning procedures, and restarting of the ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Among these products, wafers have already been the subject of some studies (Huber and Schoenlechner, 2016;Mert et al, 2015;Dogan, 2006;Dogan et al, 2016). In the literature, there are no reports concerning the production of gluten-free wafers containing freeze-dried fruits as natural colorants.…”
Section: Introductionmentioning
confidence: 99%
“…Among these products, wafers have already been the subject of some studies (Huber and Schoenlechner, 2016;Mert et al, 2015;Dogan, 2006;Dogan et al, 2016). In the literature, there are no reports concerning the production of gluten-free wafers containing freeze-dried fruits as natural colorants.…”
Section: Introductionmentioning
confidence: 99%
“…Muffins (16.3 g/100 g) and waffles (15.4 g/100 g) also had high-sugar contents. Gao et al (2017) and Huber and Schoenlechner (2017) reported similar sugar contents (20.7 and 15.9 g/100 g, respectively) in muffins and waffles. The Korea Food and Drug Administration (KFDA, 2009) and Yang et al (2009) reported that waffles sold near schools had a high-sugar content (20.5 g/100 g).…”
Section: Resultsmentioning
confidence: 73%
“…However, it is low in nutrients. During study [7], gluten-free wafer formulations were developed by using corn, rice, and buckwheat flour, xanthan, and guar gum as an alternative product for patients with celiac disease. There are data on the use of gluten-free types of flour in the production of wafer sheets, but they affect the viscosity of the dough in different ways, although in general, the impact on the consumer properties of wafer sheets is positive [8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%